Adaptation of Aquatic Microbial Communities to Quaternary Ammonium Compounds - Ventullo, Roy M. (1986)
The effects of long-chain (C(12) to C(18)) quaternary ammonium compounds (QACs) on the density, heterotrophic activity, and biodegradation capabilities of heterotrophic bacteria were examined in situ in a lake ecosystem. Monoalkyl and dialkyl substituted QACs were tested over a range of concentrations (0.001 to 10 mg/liter) in both acute (3 h) and chronic (21 day) exposures. In general, none of the QACs tested had significant adverse effects on bacterial densities in either acute or chronic studies. However, significant decreases in bacterial heterotrophic activity were noted in acute studies at QAC concentrations from 0.1 to 10 mg/liter. Chronic exposure of lake microbial communities to a specific monoalkyl QAC resulted in an adaptive response and recovery of heterotrophic activity. No-observable-effect level in the adapted populations was >10 mg/liter. Chronic exposure also resulted in significant increases in the number and activity of bacteria capable of biodegrading the material. The increase in biodegradation capability was observed at low (microgram per liter) concentrations which are approximately the same as realistic environmental levels. In general, our studies indicated that exposure of lake microbial communities to QACs results in the development of adapted communities which are less sensitive to potential toxic effects and more active in the biodegradation of these materials.